Curriculum projects, learner agency and young people's fullness of life. Issue 2 (30th May 2020) - Raffo, Carlo; Roth, Wolff‐Michael; Buck, Rob; Hodson, Patsy
Abstract : A recent article in this journal suggests that although learner agency is central to understanding young people's engagement with the curriculum, there is little exploration of such ideas in the field. In response, they argued for an Archerian approach to learner agency and a contextually, interpersonally, intra‐personally and temporally situated curriculum that suggests the centrality of young people's educational reflexivity and associated learner agency for mediating the structural aspects of their educational lives. We reflect on this thinking through the lens of a curriculum project the design of which was similarly inspired by the work of Margaret Archer. We do so through the eyes of Grace, one of the young participants in the project. We learn from Grace that learner agency and curriculum engagement is not, as Archer's framework suggests, a substantively self‐authored reflexive endeavour that can be made amenable to change through a bespoke curriculum project. Rather learner (agency) in young people might be more accurately theorised in pragmatist terms as something embedded in the drama of the fullness of their everyday lives of which the curriculum represents just a tiny part. The implications for the field of learner agency and curriculum studies are discussed.